Assessing ISO/IEC29110 by means of ITMark: results from an experience factory. Issue 11 (21st June 2016) - Larrucea, Xabier; Santamaría, Izaskun; Colomo‐Palacios, Ricardo
Abstract: ISO/IEC 29110 is intended to help very small entities in improving their software processes. However, this standard is not the only initiative devoted to help organizations in these matters. For instance, ITMark is an established method with an important background in terms of number and diversity of assessments. The aim of this paper is to present a method to assess ISO/IEC 29110 by means of the evaluation performed under the ITMark certification schema built upon an experience factory. To do so, in this paper, authors present, firstly, a mapping for ITMark to ISO/IEC 29110 and, secondly, a study to test the applicability of the assessments made by ITMark in the ISO/IEC 29110 environment taking into account the previous mapping. The main conclusion from this industrial experience is that ITMark can be used as a method for assessing very small entities. Copyright © 2016 John Wiley & Sons, Ltd.